Pectin Extraction of Jackfruit Peel as a Biopolymer Potential with Microwave Assisted Extraction Method - Muhammad Khairul Afdhol; Fiki Hidayat; Tomi Erfando; Dita Putri Purnama (Scientific Contributions Oil and Gas, 2024)
Polyacrylamide and polysaccharides are commonly used polymers, but they have certain disadvantages. Hydrolyzed polyacrylamide (HPAM) is particularly susceptible to harsh reservoir conditions, including high shear forces, salinity, and temperature. Xanthan gum biopolymer has drawbacks, such as high cost and susceptibility to reservoir biodegradation. In contrast, pectin is a viable alternative owing to its excellent biodegradability, natural decomposition, transparency, good elongation properties, and strong gel-forming ability. In this study, we characterize and analyze the rheology of biopolymers derived from jackfruit skin. Jackfruit peel, a waste product, contains a high pectin content of 23.47%, which can be extracted through microwave assisted extraction (MAE). The MAE method combines microwave and solvent extraction, offering the advantage of a fast extraction time. The resulting biopolymer is expected to enhance water viscosity and meet characterization standards for petroleum applications. FTIR test results reveal the functional groups that constitute the pectin compounds. Biopolymer concentrations used were 1,000, 2,000, and 3,000 ppm. The viscosity values of pectin were 0.503, 0.565, and 0.592 cp, while the viscosity values of xanthan gum were 1.266, 3.096, and 13.13 cp. Pectin has a lower viscosity compared to xanthan gum, and the viscosity of both biopolymers decreases as salinity increases. The reduction in viscosity for pectin during thermal testing was 26%, 28%, and 30%, whereas for xanthan gum, it was 21%, 49%, and 42%. This decrease in viscosity is attributed to the high shear rate and high salinity, which disrupt gel formation.Â